(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research, legal issues related to divorce of a Buddhist monk after ordination under the Civil and Commercial Code, was qualitative research employing documentation method. Data were collected to conduct content analysis having objectives were 1) to study legal principles and reasons as well as collecting ideas and principles of legal issues related to the divorce of Buddhist monks; 2) to study the legal issues and challenges under the Civil and Commercial Code; 3) to seek solutions for such issues related to the divorce; and 4) to analyze and compare those issues related to the divorce. Results of the study showed that cohabitation under the registration of marriage is significant according to the legal consequences. With the divorce, it is as well important, in particular, to economic, political, religious, cultural, and customs beliefs. In case of Buddhist monks, the Civil and Commercial Code has specific provision regarding divorce that applies to the monks and the laity despite the slight change. Still, provisions of the Civil and Commercial Code must be complied and not in contradiction to Vinaya, the code of monastic discipline, which is a law of the Buddhist monk. Some activities or affairs that may be done under the Civil and Commercial Code are prohibited by regulations of the Sangha, especially in regard to the divorce of the Buddhist monk under Section 1516 of the Civil and Commercial Code. The marriage is voidable or void and result of divorce shall be enforced. In case of a child born of voidable marriage, the result of divorce by judgement of the Court and divorce with mutual consent of a Buddhist monk must be complied with Section 1516 of the Civil and Commercial Code, and some issues remain. The study led to guidelines for the divorce of the monk and the laity. It was found that the law ought to be amended to be more apparent and appropriate for the current circumstances.